Comparing between low and high entrepreneurial tendencies across various characteristics of the firms - Abdul Majid, Izaidin; Dora, Mohd Taib; Ismail, Kamariah (2008)
Young firms, i.e. below 5 years, are generally perceived as ambitious for high growth. As high growth may be associated with high entrepreneurial propensity it is reasonable to assume that younger firms tend to be more entrepreneurial in order to achieve high growth. This research looks into a wide array of firms' characteristics in the pursuit of identifying which characteristics have higher tendency towards opportunity-based management, i.e. Entrepreneurial Management. Primary data were collected through postal and email surveys and were used in the data analysis process using SPSS. As this study is aimed to cover the whole population of the Malaysian-owned MSC status companies and the respondents were the owner-managers, CEOs or other senior management of the firms, a survey method using postal, self-administered questionnaire was deemed practical. This research reveals that within the sample firms highly entrepreneurial firms tended to be aged less than 3 years, still having their original founder(s) on board, had 10 or fewer employees, were owned by other firms, not originally founded in the MSC region, had sales abroad, were mainly engaged in product manufacturing and were founded by individuals. Secondly, this research supported the generally accepted assumption that firms that were managed entrepreneurially, which demonstrate high propensity toward pursuing business opportunities, do have some significant positive impact on their performance.